1988
DOI: 10.1210/mend-2-10-946
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulation of c-fosMessenger Ribonucleic Acid

Abstract: Acute administration of 17 beta-estradiol to immature female rats elicits a rapid and striking increase in the size of the uterus. This increase in size to caused by both hypertrophy and hyperplasia in the epithelial, stromal, and myometrial cells in the uterus. Previous studies have shown that induction of mRNA for the epidermal growth factor receptor, the cellular homolog of the erb-B oncogene, occurs early during estrogen-stimulated uterine growth. We report here that estradiol causes a very rapid induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
0
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(84 citation statements)
references
References 33 publications
5
78
0
1
Order By: Relevance
“…Such a finding is congruent with the earlier observation that estrogens stimulate growth of the pituitary through replication of the prolactin-secreting cells in F344 rats but not in outbred rat strains (11-13). We also found that the uterine epithelium of F344 rats but not that of S-D rats exhibited a hypertrophic response to BPA administered in low doses (2 (15)(16)(17)(18). The induction of these genes is believed to play a key role in cell proliferation (19,20).…”
mentioning
confidence: 61%
“…Such a finding is congruent with the earlier observation that estrogens stimulate growth of the pituitary through replication of the prolactin-secreting cells in F344 rats but not in outbred rat strains (11-13). We also found that the uterine epithelium of F344 rats but not that of S-D rats exhibited a hypertrophic response to BPA administered in low doses (2 (15)(16)(17)(18). The induction of these genes is believed to play a key role in cell proliferation (19,20).…”
mentioning
confidence: 61%
“…Our results, however, indicate that both DES and Tx act as ER inducer in the uterus and vagina in both neonatal and ovariectomized adult mice, although ER mRNA induction time of Tx is slower than that of DES in neonatal mice. Estrogens including DES evoke the early response of genes, jun and fos proto-oncogenes, whose products control the cell cycle (Loose-Mitchell et al, 1988;Weisz and Bresciani, 1988;Kamiya et al, 1995). Tamoxifen also raises the uterine activity levels of these protooncogenes in rats (Kirkland et al, 1993;Nephew et al, 1993) and in mice (Nishimura et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen-mediated hyperpolarization of PAG-RVM neurons would provide a direct mechanism whereby morphine failed to elicit Fos in PAG-RVM neurons. Alternatively, as the gene encoding Fos contains an estrogen response element (Loose-Mitchell et al, 1988,Wang et al, 2003, changes in cycle status may have potentially influenced the ability of morphine to induce Fos in PAG-RVM neurons in females. Lastly, estradiol has also been shown to induce MOR internalization (Eckersell et al, 1998,Sinchak and Micevych, 2001,Micevych et al, 2003,Mills et al, 2004; this would limit the amount of receptor available for ligand binding and would thereby potentially decrease morphine's ability to induce Fos in PAG-RVM neurons.…”
Section: The Pag-rvm Circuit Is Preferentially Activated In Male Ratsmentioning
confidence: 99%